Designs of adder circuit in QCA - Sasamal T.N.; Singh A.K.; Mohan A. (My University, 2025)
In this chapter, we discuss two different designs of QCA Ripple Carry Adders by customizing the fundamental block, i.e., the full adder circuit. We start the discussion with designing RCA using 5-input majority gate-based full adder. Further, designs are evolved considering a compact form full adder that relied on a novel XOR structure. Parts of the analysis presented in this chapter have been discussed in [1, 2]. © Springer Nature Singapore Pte Ltd 2020.